Assessment of local skin reactions with a sequential regimen of cryosurgery followed by ingenol mebutate gel, 0.015%, in patients with actinic keratosis - Goldenberg, Gary (Clin Cosmet Investig Dermatol, 2014)
Lesion-directed and field-directed therapies are used to treat actinic keratosis (AK). Therapeutic approaches that combine both types of therapies may improve the successful elimination of AKs. A randomized, double-blind, vehicle-controlled study evaluated the safety, tolerability, and efficacy of topical field treatment with ingenol mebutate gel, 0.015%, after cryosurgery to AKs on the face and scalp. Patients with 4–8 visible discrete AKs in a 25-cm(2) contiguous area received cryosurgery of all AKs at baseline. After a 3-week healing period, patients applied ingenol mebutate gel, 0.015%, or vehicle gel once daily for 3 consecutive days to the treatment area. The incidence, severity, and time course of the development and resolution of local skin reactions were measured from baseline to week 11. Local skin reactions peaked shortly after completion of ingenol mebutate treatment and generally resolved within 2 weeks. The mean (95% confidence interval) composite score (maximum range, 0–24) for these reactions was higher in patients with treatment of AKs on the face, 9.3 (8.5–10.1), as compared with the scalp, 5.8 (4.3–7.4). Erythema and flaking/scaling were the major contributors to the composite local skin reaction score. These results show that local skin reactions associated with ingenol mebutate treatment of the face or scalp are well tolerated after recent cryosurgery.